Piglets' acute responses to local anesthetic injection and surgical castration: Effects of the injection method and interval between injection and castration - Coutant, Mathilde; Malmkvist, Jens; Kaiser, Marianne; Foldager, Leslie; Herskin, Mette S. (Frontiers in Veterinary Science, 2022)
Although applied in some countries, efficacy of local anaesthetics based on procaine to mitigate acute responses to piglet castration remains questioned. This paper presents results from a factorial study examining the effects of two methods of injection of a procaine-based drug (intra-funicular, IF, versus intra-testicular, IT), and four intervals between drug injection and castration (2.5, 5, 10 and 30 min) on acute responses of 3-4 day old piglets. The study involved 597 male piglets, and 13 treatments: surgical castration without anaesthesia (CC), local anaesthesia followed by castration involving all combinations of injection method and interval, and sham handling separated by the same four intervals (SH). Responses of piglets to drug injection, castration and sham handling were evaluated based on quantification of intra-procedural vocalisations and leg movements, as well as saliva cortisol concentration in samples taken before and after castration. No differences were found between IF and the simpler IT injection method. Intervals of 2.5 or 30 min led to stronger piglet responses than the other intervals. Overall, treatments involving anaesthesia led to significantly stronger responses than sham handling, during both injection and castration. All treatments, even sham handling, led to a significant increase in saliva cortisol, with no differences between anaesthesia treatments and controls. Based on these results, castration 5-10 min after intra-testicular injection of procaine seems to be preferable as compared to the other treatments tested. However, piglets still showed measurable signs of pain and stress during both injection and castration, while handling alone (including the use of a castration bench) triggered a noticeable stress response. In light of these findings, the overall benefit of the procedure in terms of piglet welfare remains arguable.